PENGARUH TINGKAT RELIGIUSITAS, KUALITAS LAYANAN TERHADAP KEPUTUSAN MENABUNG DAN INFORMASI SEBAGAI VARIABEL MODERATING - Irham Pakkawaru (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2018)
This study aims to find empirical evidence regarding the effect of the level of religiosity, the quality of service on saving decisions of the Faculty of Economics students in Islamic banking and information as a moderating variable. The sample used was students majoring in economics in the city of Palu. The type of data used is primary data with analysis techniques using multiple linear regression and hypothesis testing using simultaneous analysis (F test) and partial (t- test). The results of this study indicate that simultaneously the level of religiosity and service quality variables significantly influence saving decisions. Partially only the service quality variable (X2) has a significant effect on saving decisions (Y). While the religiosity level variable does not have a significant influence on saving decisions (Y), and Information does not moderate or not as a moderating variable.